Clinical features associated with early drop-out among outpatients with unipolar and bipolar depression. (April 2021) - Fornaro, M.; Novello, S.; Fusco, A.; Anastasia, A.; De Prisco, M.; Mondin, A.M.; Mosca, P.; Iasevoli, F.; de Bartolomeis, A.
Abstract: Drop-out from follow-up visits carries significant burden for people diagnosed with depression. The present study assesses multiple clinical moderators of drop-out among depressed outpatients. We retrospectively followed-up 131 outpatients over 6 months: 78 major depressive disorder (MDD), and 53 bipolar disorder (BD-I = 24; BD-II = 29) patients diagnosed according to the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition. Participants were assessed with standard rating scales administered by experienced psychiatrists. Upon descriptive and Cox regression analyses, 17/53 BDs (32%) dropped-out; the overall survival time until drop-out was 57.94 ± 17.79 days. BD drop-outs were younger, had an earlier age at onset, shorter illness duration, lower rates of lifetime obsessive-compulsive disorder/suicidal behavior, higher rates of substance use disorder (SUD), anxious and mixed features of depression compared to BDs attending up to six months. Among MDD patients, 10/78 cases (13%) dropped-out by month-6 with an average survival of 42.40 ± 16.45 days. Earlier age of onset, younger age, positive family history for mood disorders, lower rates of lifetime generalized anxiety disorder were significantly more frequent among drop-outs than completers, as opposite to SUD, and lifetime recurrent depression. Older age predicted lower drop-out among BDs and MDDs, although with almost null hazard ratio (HR) = 0.928, p < 0.01 vs. HR = 0.941, p < 0.01, respectively. Higher rates of lifetime SUD predicted higher drop-out rates by month-6 among MDDs (HR = 5.477, p = 0.02). Limitations of the study: retrospective design, small sample size, lack of objective measures of treatment-adherence/mood rating during follow-up. Drop-out is common in the real-world setting, warranting specific interventions since the beginning of the treatment. Highlights: Drop-out among depressed outpatients is common and burdensome. Substance use disorder predicts early drop-out in unipolar depression. Younger age predicts early drop-out in unipolar and bipolar depression. Specific interventions should promote the engagement of vulnerable patients.